MAKE A MATCH MODEL, HIGH ORDER THINKING SKILLS QUESTIONS, AND THE STUDENTSâ CURIOSITY - Sari, Putri Permata; Budiyono, Budiyono; Slamet, Isnandar (Journal on Mathematics Education)
Geometry has an important role in mathematics study. Make A Match high order thinking skills questions aims to improve the students curiosity and students HOTS for understanding the material. This research aims to find out the effect of learning model and emotional intelligence toward students mathematics achievement.This research is quasi-experimental research with a 2x3factorial design. Population on this research was State Senior High School students on 11th grade in Sukoharjo Regency, Central Java, Indonesia. The data collection were collected by using questionnaire and test. Furthermore, data were analyzed by two-way ANOVA. According to the research findings, shows that: students taught by MAM HOTS questions have better mathematics learning achievement than those taught by using direct learning model. Students having high emotional intelligence category have better mathematics learning achievement than those having medium and low emotional intelligence category, and they who have medium emotional intelligence category have mathematics learning achievement as good as those with low emotional intelligence category.Therefore, MAM HOTS questions can improve students learning achievement.